A Retrospective on the classical gold standard, 1821-1931 - Bordo, Michael D.; Schwartz, Anna J. (Anna Jacobson), 1915-2012 (Conference report (National Bureau of Economic Research), 1984)
This is a timely review of the gold standard covering the 110 years of its operation until 1931, when Britain abandoned it in the midst of the Depression. Current dissatisfaction with floating rates of exchange has spurred interest in a return to a commodity standard. The studies in this volume were designed to gain a better understanding of the historical gold standard, but they also throw light on the question of whether restoring it today could help cure inflation, high interest rates, and low productivity growth. The volume includes a review of the literature on the classical gold standard.